The Archaeology of Jerusalem — Between Post-Modernism and Delegitimization. (August 2013) - Seligman, Jon
<x content-type="archive" xml:space="preserve">Abstract</x> The study of the motivations, influences, and agendas of Israeli archaeology has always been the centre of heated debate, the profession today finding itself under the full, and usually highly critical, glare of modern archaeological theory and/or political polemics. This paper addresses the motivations of some these critics and from under the mesh of often over-stated argumentation, tries to provide a more level appreciation of current archaeological work in Jerusalem. Quite contrary to the impression given by some of the recent scholarship, it is argued that the great majority of the published and excavated archaeology of Jerusalem of the past decades presents the finds of the multiplicity of periods of the city's history, quite divorced from overt and even covert influence of the surrounding volatile political situation.